Integration of Halal Literacy and Food Safety Aspects in Elementary School Canteens: A Case Study of Halal Critical Points and a Risk-Based Educational Approach - Ira Sukmawati Abidin; Neneng Windayani (LP2M IAIN Palopo, 2026)
Elementary school canteens play a vital role in providing daily meals for the school community. However, adherence to halal principles is crucial.ṭHalal safety has not been fully guaranteed, both in terms of ingredients, processes, and packaging. This study aims to identify halal critical points (CCPs) and the level of halal literacy of elementary school students, and formulate risk-based improvements in accordance with the Halal Product Assurance regulation (Law No. 33/2014) and BPOM provisions on food packaging. A qualitative-quantitative research design was used through structured observations, interviews, and halal literacy questionnaires with 5 canteen operators, 120 students, and 3 teachers in Bandung Regency. Risk analysis based on severity × likelihood values ​​resulted in four main CCPs: (1) washing cutlery in the toilet; (2) exposure to flies on food; (3) use of styrofoam for hot food; and (4) low student halal literacy (average score 54.3%). Recommendations for improvement include the establishment of a dedicated cutlery washing zone, vector control, replacing hot packaging with safe materials (PP5/food-grade paper), and halal education.ṭayyib integrated into science learning. This study emphasizes the integration of the halal risk mapping system.ṭayyib in the context of elementary school canteens, which has not been widely implemented before, as well as the proposal of a halal literacy-based education model integrated into the science curriculum to increase halal awareness among students. The results of this study provide a model for halal school canteen practices.ṭrisk-based ayyib that can be implemented in other schools as part of the Healthy School program and supports the National Halal Product Guarantee.